Influence of rice husk based nanosilica in rheological and stability of binary mixture fluid - Wan, Mohd Eqhwan Iskandar; Ruey Ong, Huei; Khan, Maksudur Rahman Md; Ridzuan, Ramli (Elsevier Ltd, 2022)
In this work, an organic derived nanofluid has been developed from bio-origin resources. Rice husk derived nanosilica has been prepared via a simple two-steps thermal process with minimum energy (low temperature and reaction time) using solar assisted plasma furnace. A low density nanosilica (112.3 kg/m3) has been prepared. The nanosilica was characterized by using TEM and XRD to verify the surface morphology and crystallinity structure respectively. Nanofluids comprised of nanosilica and EG/water binary mixture has been prepared at various concentration such as 0.2 – 1.0 vol% of nanosilica. Flow curve of nanofluids showed that at minimum inclusion of nanosilica enhanced the stress of the fluid significantly. Moreover, dynamic viscosity measure shows that addition of nanosilica stabilized the properties of the fluid compared to virgin fluid. The present product offers greener approach for nanofluids which derived from natural resources and environmentally friendly (very low percentage of nanoparticle, 0.2 vol% equivalent to 0.0215 wt%). Apart from that, the stability and rheological properties fluids were improved with the inclusion of nanoparticle.